Dinamika Tekanan Teman Sebaya dalam Konstruksi Perilaku Bermasalah pada Remaja - Dwi Septia Ningsih; Nabila Dwi Putri; Zakia Rahmadania; Indah Permata Sari; Nofia Lolita; Tria Yunita; Rizki Novirson (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the dynamics of peer pressure as a factor that forms problematic behavior in adolescents. This study uses a literature review method with more than 19 relevant journals. The selected journals followed inclusion criteria that focused on adolescents, peer pressure, and problematic behaviors within a specific time frame. The results of the study showed that peer pressure contributes to problematic behaviors such as aggressive behavior and social violence (bullying, cyberbullying, aggressiveness, disruptive behavior), addictive and health-risking behaviors (smoking, alcohol consumption/drinking behavior), violations of academic/school norms (truancy, juvenile delinquency), online/sexual risky behavior (cybersex), and internal psychological problems (decreased self-confidence). The psychosocial dynamics found included the need for acceptance, group conformity, low self-control, and weak family support. These influences can be direct or indirect through the internalization of group values. These findings confirm that problematic behaviors are not formed singularly, but from complex interactions between individual factors and the social environment. Therefore, prevention efforts require a collaborative approach between families, schools, and the community.